In Plain Sight or Just Plain Obscured?: A Review of Professional Evaluation Associations' Frameworks for Evaluation Practice Supporting Equity, Diversity and Inclusion (EDI) - Jane Whynot (The Evaluation Center at Western Michigan University, 2023)
With an increasing focus on integrating equity, diversity and inclusion (EDI) in evaluation practice and products, there is an accompanying need to examine what structural supports exist that are provided by professional evaluation associations. This contribution systematically examines the competencies of five professional evaluation associations from Africa, Australia, Europe and North America to identify how evaluators can align integrating EDI in thei evaluation practice to professional competency domains. Also offered is a summary of thoughts on training opportunities for integrating EDI given review findings. Professional evaluation association websites were reviewed during May through to July of 2022. Content was downloaded into an Excel spreadsheet, and organized for EDI review purposes by competency domains, subdomains which occurred during August and September of 2022. The presentation of EDI content in evaluator competencies was found to be highly varied; variations were found in tone/theme, principles, and domains and subdomains.